If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 75 = 23 Reorder the terms: 75 + 4x = 23 Solving 75 + 4x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + 4x = 23 + -75 Combine like terms: 75 + -75 = 0 0 + 4x = 23 + -75 4x = 23 + -75 Combine like terms: 23 + -75 = -52 4x = -52 Divide each side by '4'. x = -13 Simplifying x = -13
| n-15x=6 | | (X-6)(X-6)3=147 | | 5m^2-26m-24=0 | | Y-8/3-1/3x2/3 | | 1+log(3x-1)=log(2x+1) | | 3x^2=15x+18 | | 3x(3x-10)=-24 | | cos(6x)-cos(2x)= | | x+30=40 | | 3x-8y+6y=8 | | (3x-5)(9x+1)=0 | | 2x^2=4(x-5) | | 12x^3+20x^2-8x=0 | | -5n(5n-7)=0 | | 12x^3+20x-8x=0 | | 6(4x-8)+8=24x-40 | | 0.33=ln | | 3x+1=3(x-8) | | 2y=-1.5x+38 | | a/9-=6 | | 12y^2-2=5y | | 3x^3-x^2+36X-12=0 | | 3(2)+7y=7 | | 66x+12=24 | | (3e^2x+4)=6 | | Log(Lnx)= | | (5+H)*2=36 | | 8y+4y=8 | | (5*H)*2=36 | | 8(x-4)+5=-27 | | (z^2-16)(z^2-49)=0 | | 24x+-36=18 |